MadNIS - Neural multi-channel importance sampling - Heimel, Theo; Winterhalder, Ramon; Butter, Anja; Isaacson, Joshua; Krause, Claudius; Maltoni, Fabio; Mattelaer, Olivier; Plehn, Tilman (SciPost physics, 2023)
SciPost Journals Publication Detail SciPost Phys. 15, 141 (2023) MadNIS - Neural multi-channel importance sampling